Who benefits from customary justice? Rent-seeking, bribery and criminality in sub-Saharan Africa - D'Aoust, O; Sterck, O (Oxford University Press, 2016)
In many Sub-Saharan countries, customary and statutory judicial systems co-exist. Customary justice is exercised by clan leaders or local courts, and based on restorative principles. By contrast, statutory justice is mostly retributive and administered by magistrates’ courts. As the jurisdiction of the customary and the statutory systems often overlap, victims can choose which judicial system to refer to, which may lead to contradictions between rules and inconsistencies in judgments. In this essay, we construct a model representing a dual judicial system. We show that the overlap of competence encourages rent-seeking and bribery, and yields to high rates of petty crimes and civil disputes. We recommend the subsidization of the statutory judicial system, as it efficiently improves deterrence and incapacitation in the dual judicial system while minimizing corruption of customary judges. We illustrate our theoretical predictions by discussing the functioning of the Ugandan dual judicial system.